The microbiota drives diurnal rhythms in tryptophan metabolism in the stressed gut - Cassandra E. Gheorghe; Sarah-Jane Leigh; Gabriel S.S. Tofani; Thomaz F.S. Bastiaanssen; Joshua M. Lyte; Elisa Gardellin; Ashokkumar Govindan; Conall Strain; Sonia Martinez-Herrero; Michael S. Goodson; Nancy Kelley-Loughnane; John F. Cryan; et al. (Cell Reports, 2024)
Summary: Chronic stress disrupts microbiota-gut-brain axis function and is associated with altered tryptophan metabolism, impaired gut barrier function, and disrupted diurnal rhythms. However, little is known about the effects of acute stress on the gut and how it is influenced by diurnal physiology. Here, we used germ-free and antibiotic-depleted mice to understand how microbiota-dependent oscillations in tryptophan metabolism would alter gut barrier function at baseline and in response to an acute stressor. Cecal metabolomics identified tryptophan metabolism as most responsive to a 15-min acute stressor, while shotgun metagenomics revealed that most bacterial species exhibiting rhythmicity metabolize tryptophan. Our findings highlight that the gastrointestinal response to acute stress is dependent on the time of day and the microbiome, with a signature of stress-induced functional alterations in the ileum and altered tryptophan metabolism in the colon.